PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - suhardiyah, martha; Khotimah, Khusnul; Subakir, Subakir (Universitas PGRI Adi Buana, 2018)
This study aims to determine whether there is influence disclosure Sustainability Report on financial performance. The variables used are economic performance (X1), environmental performance (X2), social performance (X3) and Financial Performance (Y). This research data is secondary data obtained from company's annual report of mining sector invesment which listed in Indonesia Stock Exchange and sampling technique using purposive sampling. Methods of data analysis using classical assumption test and multiple linear regression analysis. Based on data analysis, it is concluded that partially (t test) economic performance variable got t-count equal to 4,027 and sign equal to 0,001 <0,05, hence proposed hypothesis accepted. The environmental performance was calculated by 2.879 and the sign was 0.011 <0.05, thus the proposed hypothesis was accepted. The social performance is calculated by 1,264 and the sign is 2,224> 0,05, thus the proposed hypothesis is rejected. Financial performance is influenced by economic performance, environmental performance and social performance in sustainability report of 88.3% and sisahnya influenced by other variables. Therefore, it is expected to further improve the financial performance of the company with more attention to sustainability report (sustainability report) in a row and continue to be expanded